Investigation on Foaming Ability of Modified Polyethylene Terephthalate (PET) Composites Prepared Using Compression Molding - Hua-yong Liao; Jing Gao; Guo-liang Tao; Chun-lin Liu (International Journal of Polymer Science)
An investigation was conducted on the foaming formula and production technique of polyethylene terephthalate (PET) using orthogonal design analysis and Box–Behnken response surface analysis. PET was combined with polyolefin elastomer (POE) and filled with surface-treated mica, quartz, and graphene oxide (GO). POE served as a carrier and modifier for the foaming agent, as well as a toughening agent. The addition of fillers can improve the thermal properties of PET foaming material. To do this, the blending process includes using a microsphere foaming agent on an open mill at a low temperature of 50°C for 5–6 min. After this, dicumyl peroxide (DCP) and antioxidant are added for 1 min before the specimens are removed from the open mill and flattened. The next step involves placing the specimens in a plate vulcanizing machine at 265°C and 10 MPa for 10 min to initiate the foaming process. The PET foam obtained has a density of 0.4–0.5 g/cm3, a tensile strength of 5–6.8 MPa, an elongation at break of 64–276%, and a tear strength of 5.1–14.5 N/m. Scanning electron microscope (SEM) images reveal that the PET foam contains micron-sized cells, with measurements ranging from about 107 to 273 μm. The tested samples showed that the PET foam with 50 phr of POE, 7 phr of foaming agent, and 5 phr of mica exhibited relatively good mechanical properties, including tensile strength, elongation at break, and tear strength. The thermogravimetric analysis (TGA) indicated that the thermal properties of PET foam are better than those of pure PET. The modified PET foam has many applications due to its low density and excellent properties. This study introduces a new and uncomplicated method for producing PET foam, which differs from the commonly used extrusion foaming process that involves supercritical carbon dioxide or other media.